Handbook of thin film deposition techniques, processes, and technologies - Seshan, Krishna (Elsevier ; William Andrew, 2012)
The Handbook of Thin Film Deposition is a comprehensive reference focusing on thin film technologies and applications used in the semiconductor industry and the closely related areas of thin film deposition, thin film micro properties, photovoltaic solar energy applications, new materials for memory applications and methods for thin film optical processes. In a major restructuring, this edition of the handbook lays the foundations with an up-to-date treatment of lithography, contamination and yield management, and reliability of thin films. The established physical and chemical deposition processes and technologies are then covered, the last section of the book being devoted to more recent technological developments such as microelectromechanical systems, photovoltaic applications, digital cameras, CCD arrays, and optical thin films.